Penggunaan Meme Sebagai Media Pendukung Pembelajaran IPS Dalam Menumbuhkan Minat Belajar Dan Berpikir Kritis Siswa SMP Negeri 42 Surabaya: Use of Memes as Supporting Media for Social Studies Learning in Fostering Interest in Learning and Critical Thinking of Students at SMP Negeri 42 Surabaya - Karuniawan, Jeconia Raven (Jurnal Dialektika Pendidikan IPS, 2023)
This study aims to observe and analyze the use of memes as a supporting medium for social studies learning in fostering interest in learning and critical thinking of SMP Negeri 42 Surabaya students. This research is a qualitative study using exploratory research techniques. The subjects in this study took class VII-L SMP Negeri 42 Surabaya with a total of 33 students consisting of 15 male students and 18 female students. Data collection conducted in this study used interviews, observations (learning interest observation sheets and student worksheets), and documentation. The implementation of this research was carried out for 3 meetings with the results obtained that, the use of memes as a supporting media for social studies learning is very efficient and helps students relax or provide a sense of comfort and entertainment during teaching and learning activities (KBM) which can be seen from the results of observations of learning interest which shows a presentation result of 89% and also the results of working on student worksheets (LKPD) by students who have an average score of 89 as well as, meme assignments made by students who get an average score of 81. These results show that the supporting media memes really have a positive impact which is quite good in the process of fostering interest in learning and critical thinking of students in class VII-L at SMP Negeri 42 Surabaya. The use of memes as supporting media is generally very efficient and helpful.